Looking Back, Thinking Forward: How Jewish Summer Camps Shape Youth Religious and Ethnic Identity - Birger, Allie G. (Tufts Archival Research Center, 2022)
Past research shows that in the wake of widespread structural assimilation in the mid-20th century, Jewish leaders and adults began to worry about ethnic and religious dilution. One of their “top down” responses was to strengthen community ethnic institutions, including by establishing a large network of summer camps, intended to expose Jewish youth to Jewish cultural and religious practices, as well as other young Jews. A few pioneering scholars have studied these camps specifically, focusing on their number, structure, and goals. Nevertheless, little is known about how Jewish youth understand, interpret, and make sense of their religious and ethnic identity within the context of Jewish summer camps -- from the “bottom up”, through their own perspectives. The present study utilizes in-depth interviews with 21 Jewish campers and counselors at one summer camp in 2021 to explore this question. I argue that even in a quickly secularizing society, the opportunities that Jewish summer camps present for youth encourages them to actively express their Judaism on their own accord in adulthood, regardless of previous religious background or community ties. I then discuss my argument’s implications for the existing literature and future research.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Sociology.; Advisor: Helen Marrow.; Committee: Felipe Dias, Natasha Warikoo, and Anjuli Fahlberg.